The Sophia Gray memorial Lectures and Exhibitions - Kotze, Paul (Acta Structilia, 2001)
In 1989 the University of the (Orange) Free State in Bloemfontein, SA, inaugurated an annual lecture and exhibition to highlight the contribution made by architects and architecture to society. This was named after Sophia Gray, the first professionally active architect in Bloemfontein. It is generally agreed that she was responsible for the design of the initial chapel that eventually became the Anglican Cathedral of St Andrew and St Michael in St George’s Street.